Transient Heat Transfer in a Slab with Heat Generation - Marwah, I. J.; Chopra, M. G. (Defence Science Journal, 2014)
A numerical solution has been obtained for transient thermal distribution in a slab in which chemical, electrical or nuclear energy is converted into thermal energy. An implicit scheme is used to set up the finite difference analog of the diffusion equation and the accompanying initial and boundary conditions.